2021
DOI: 10.1016/j.mtnano.2021.100131
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon damping and charge transfer pathways in Au@MoSe2 nanostructures

Abstract: Hybridization of plasmonic and excitonic elementary excitations provides an efficient mean of enhancing the optical absorption and emission properties of metal/semiconductor nanostructures and is a key concept for the design of novel efficient optoelectronic devices.Here we investigate the optical properties of 2D MoSe 2 quantum well flakes covered with Au nanoparticles supporting plasmonic resonances. Using spatially resolved confocal spectroscopy, we report the observation of a quenching phenomenon of the Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…The broad absorption band also indicates that defect states are distributed across a significant portion of the band gap. Moreover, it can be observed that the plasmon resonance of H x MoO 3 is relatively weak, although it is highly defective, implying that the hot electron recombination rate in H x MoO 3 is extremely fast. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The broad absorption band also indicates that defect states are distributed across a significant portion of the band gap. Moreover, it can be observed that the plasmon resonance of H x MoO 3 is relatively weak, although it is highly defective, implying that the hot electron recombination rate in H x MoO 3 is extremely fast. , …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it can be observed that the plasmon resonance of H x MoO 3 is relatively weak, although it is highly defective, implying that the hot electron recombination rate in H x MoO 3 is extremely fast. 40,41 SERS Performance Evaluation. The oxygen vacancy defect density in MoO 3 and H x MoO 3 was tuned using a 365 nm UV light (see the Tuning Oxygen Vacancy by UV Light Section in Supporting Information and Figure S1).…”
Section: Synthesis and Characterization Of Moomentioning
confidence: 99%
“…For example, AuNPs are assembled on the surface of TMDCs through the gold sulfhydryl bond (Au-S bonds) ( Kong et al, 2020 ) generated between the coordinated structure of MoS 2 and AuNPs ( Parlak et al, 2017 ). Recent studies have proved that the deposition of metal nanoparticles on TMDCs may change the electronic, optical, and vibrational properties of the TMDCs layer ( Abid et al, 2021 ). Zhang et al (2016) demonstrated the strain effect induced by metal nanoparticles deposited on the MoS 2 layer using surface-enhanced Raman scattering (SERS).…”
Section: Biosensors Based On Covalent Interactions On the Surface Of ...mentioning
confidence: 99%
“…The increasing demand of novel electronic and optoelectronic applications has motivated deeper explorations of low dimensional materials, 1 nanoparticles, 2,3 and their interfaces. 2,4 In the two-dimensional materials family, 5 monolayer transition metal dichalcogenides (TMDs) have found a special place due to their direct band gap in the visible range, chemical stability, and reasonable charge mobilities. 5 Recent progress in nanoparticle preparation techniques 6 has enabled TMD heterojunctions with metallic and semiconducting nanoparticles aiding physicists, chemists, biologists, and materials scientists to explore the intimate interaction of nanostructures with monolayer semiconductors.…”
Section: Introductionmentioning
confidence: 99%